The Effect of Gamification on Customer Satisfaction through Customer Engagement on the Marketplace - Puspasari, Shafa' Annisa; Wilujeng, Ita Prihatining; Ali, Asiah (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Malang, 2024)
The rapid growth of the internet has led to the rise of the marketplace industry in Indonesia. Quite a few of these companies are competing to engage with their users and satisfy their customer, one of which is through gamification. This research aims to determine the effect of gamification on customer satisfaction through customer engagement on marketplace users, both directly and indirectly. The method used is a quantitative approach with a descriptive and explanatory research types. The data collection technique uses a questionnaire whose validity and reliability have been tested. The research sample was 200 respondents. The analysis technique used descriptive statistical analysis and Partial Least Square (PLS). Through this research, it is proven that gamification directly has a positive and significant effect on customer satisfaction and customer engagement. Customer engagement also has a direct, positive and significant effect on customer satisfaction. Gamification indirectly has a positive and significant effect on customer satisfaction through customer engagement. Thus, it can be concluded that gamification influences customer satisfaction both directly and indirectly through customer engagement in the marketplace.